RamA upregulates the ATP-binding cassette transporter mlaFEDCB to mediate resistance to tetracycline-class antibiotics and the stability of membranes in Klebsiella pneumoniae - Xiaoyu Zhao; Yixin Zhang; Mohan Ju; Yang Yang; Haoqi Liu; Xiaohua Qin; Qingqing Xu; Min Hao (Microbiology Spectrum)
ABSTRACT RamA is an intrinsic regulator in Klebsiella pneumoniae, belonging to the AraC family of transcription factors and conferring a multidrug resistance phenotype, especially for tetracycline-class antibiotics. The ATP-binding cassette transporters MlaFEDCB in bacteria play essential roles in functions essential for cell survival and intrinsic resistance to many antibiotics. We found deletion of ramA resulted in a fivefold decrease in the transcriptional levels of the mlaFEDCB operon. After complementation with ramA, the transcriptional levels were comparable to those of wild-type strain. Furthermore, an electrophoretic mobility shift assay showed that RamA could bind to the promoter region of mlaEFDCB operon, which confirmed RamA is an activator of mlaEFDCB operon. The mlaEFDCB operon could mildly mediate resistance to the tetracycline family of antibiotics under RamA regulation. The MIC (minimum inhibitory concentration) of tigecycline decreased fourfold, and the MIC of doxycycline, minocycline, and eravacycline decreased twofold after mlaE-knockout. The ramA- and mlaE-knockout strains exhibited greater sensitivity to sodium dodecyl sulfate (SDS)-EDTA than the wild-type. Growth of ΔramA cells was severely compromised in 0.25/0.5% SDS and 0.55 mM EDTA, and this sensitivity was restored by complementation with ramA and mlaE. This study demonstrates that RamA can directly regulate the malEFEDCB operon, thereby mediating resistance to tetracycline-class antibiotics, contributing to the stability of bacterial membranes in K. pneumoniae. We identified a novel signal pathway in which RamA mediates multidrug resistance of K. pneumoniae, leading to new ideas for the development of novel antimicrobial therapeutics, therefore deserving further comprehensive study.IMPORTANCEMultidrug-resistant and extensively drug-resistant Klebsiella pneumoniae have emerged as significant global health concerns resulting in high mortality rates. Although previous research has investigated the maintenance of lipid asymmetry (Mla) pathway, the extent to which it mediates antimicrobial resistance in K. pneumoniae and the underlying upstream regulatory mechanisms remain unclear. In this study, we sought to determine at the molecular level how the AraC-type global regulator RamA directly regulates mlaFEDCB, which mediates resistance to tetracycline-class antibiotics and the stability of bacterial membranes in K. pneumoniae.